2015
DOI: 10.1007/s00787-015-0705-5
|View full text |Cite
|
Sign up to set email alerts
|

Bully/victims: a longitudinal, population-based cohort study of their mental health

Abstract: It has been suggested that those who both bully and are victims of bullying (bully/victims) are at the highest risk for adverse mental health outcomes. However, unknown is whether most bully/victims were bullies or victims first and whether being a bully/victim is more detrimental to mental health than being a victim. 4101 children were prospectively studied from birth and structured interviews and questionnaires were used to assess bullying involvement at 10 years (elementary school) and 13 years of age (seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
88
1
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(110 citation statements)
references
References 68 publications
11
88
1
10
Order By: Relevance
“…Those children were at greater risk of debilitating depressive/dysthymic symptoms or anxiety and of suicidality in adolescence than less severely victimized children, even after we accounted for a plethora of confounders assessed throughout childhood. Thus, our results, along with those of many other studies, 4,5,8,16,34 suggest that severe peer victimization may contribute to the development of mental health problems in adolescence. Therefore, it is important to prevent severe victimization early in the lifespan.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Those children were at greater risk of debilitating depressive/dysthymic symptoms or anxiety and of suicidality in adolescence than less severely victimized children, even after we accounted for a plethora of confounders assessed throughout childhood. Thus, our results, along with those of many other studies, 4,5,8,16,34 suggest that severe peer victimization may contribute to the development of mental health problems in adolescence. Therefore, it is important to prevent severe victimization early in the lifespan.…”
Section: Discussionsupporting
confidence: 84%
“…It has been shown that a substantial proportion of those who have been victimized have also bullied others. 7,16 Because perpetrators tend to display higher levels of aggression 7 and conduct problems, 17 we tested whether victimization increased the risk of symptoms of mental illness above and beyond the perpetration of victimization.…”
Section: Resultsmentioning
confidence: 99%
“…There is now ample evidence that peer victimization is a childhood trauma that negatively affects psychological function both concurrently and longitudinally [38][39][40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
“…Both sexual abuse and suicidal behavior are clearly of great concern in their own right, over and above their possible associations with particular diagnostic categories. As another example from this issue of ECAP, Lereya et al [10] found that early bullying and victimization were associated with various mental health problems at age 18. Articles by Comasco et al and Ortuno-Sierra et al provide additional examples of transdiagnostic approaches.…”
Section: Transdiagnostic Heterogeneitymentioning
confidence: 99%